Gallstones - Zainul Azlan, Nurhazirah; Md. Isa, Muhammad Lokman; Ahmad Arifin, Syamsul; Othman, Noratikah; Abd. Rashid, Norlinda; Jainlabdin, Mohd Hanif; Abdul Razak, Redzuan Nul Hakim; Abd. Jalil, Mohd. Azri; Ahmad, Azmir; Tengku Zakaria, Tengku Muhamad Faris Syafiq (2021)
The PBL module consists of 2 triggers; Trigger 1 was the description of a patient's complaint and Trigger 2 was the patient's history and physical examination. This PBL aims to expose the student to the anatomy and physiology of the gastrointestinal tract (Gill and reproductive system; and discuss the pathophysiology, risk factors, and complications of gallstones.